Visual outcomes and treatment adherence of patients with macular pathology using a mobile hyperacuity home-monitoring app: a matched-pair analysis. Issue 12 (23rd December 2021) - Gross, Nico; Bachmann, Lucas M; Islam, Meriam; Faes, Livia; Schmid, Martin K; Thiel, Michael A; Schimel, Andrew; Sim, Dawn A
Abstract : Objective: We compared patients with neovascular age-related macular degeneration (nvAMD), diabetic macular oedema (DMO) and other macular pathologies testing their vision with the hyperacuity home-monitoring app Alleye to patients not performing home-monitoring regarding clinical outcomes and clinical management. Design: Matched-pair analysis. Setting: Retina Referral Centre, Switzerland. Participants: For each eye using Alleye, we matched 2–4 controls not using home-monitoring based on age, gender, number of previous intravitreal injections (IVI), best corrected visual acuity (BCVA) (Early Treatment Diabetic Retinopathy Study letters), central macular thickness (CRT) and time point of enrolment, using the Mahalanobis distance matching algorithm. We included 514 eyes (288 patients); 107 eyes with nvAMD using home monitoring and 218 controls not using home monitoring, 25 eyes with DMO (n=52 controls) and 40 eyes with miscellaneous conditions (n=72 controls). 173 eyes (33.7%) received no IVI during follow-up. Main outcome measures: Improvement of ≥5 letters, number of injection visits and treatment retention after correcting for differences in baseline characteristics with multivariate analyses. Results: The mean follow-up duration was 809 days (range 147–1353) and the mean number of IVI/year among treated eyes was 6.7 (SD 3.1). Mean age at baseline was 70.4 years (SD 10.9), BCVA was 77.6 letters (SD 11.6) and CRT was 263.6 µm (SD 86.7) and was similar between patients using and not using home monitoring. In multivariate analyses, patients using home monitoring had a higher chance to improve visual acuity by ≥5 letters (OR 1.67 (95% CI 1.01 to 2.76; p=0.044)) than controls. Treated eyes using home monitoring had less injection visits/year (−0.99 (95% CI −1.59 to −0.40; p=0.001)) and a longer treatment retention +69.2 days (95% CI 2.4 to 136.0; p=0.042). These effects were similar across retinal pathologies. Conclusions: This data suggest that patients capable of performing mobile hyperacuity home monitoring benefit in terms of visual acuity and discontinue treatment less often than patients not using home monitoring.